Factors Associated with Coexisting Forms of Malnutrition (Stunting and Wasting) in Under-Five in Southeast Sulawesi - Aisyah Nurul Hidayah; Suyatno Suyatno; Apoina Kartini (Media Kesehatan Masyarakat Indonesia, 2025)
The presence of more than one type of nutritional disorder in a person's body is called Coexisting Forms of Malnutrition (CFM). Children with CFM, such as those experiencing stunting, wasting, and underweight, 12.3 fold risk of death (CI=7.67-19.28) compared to healthy children. Southeast Sulawesi has the tenth highest prevalence of these cases. This study used secondary data based on the Indonesian Nutrition Status Survey (SSGI) 2022 with a cross-sectional design using complex sample analysis. The sample was children under five from Southeast Sulawesi Province, with a final sample size of 8,518 children analyzed. The median age of the sample was 32 months, most of them were male (50.5%), the median birth weight was 3,128.8 grams, and most of their nutritional intake was not diverse (92.1%). Bivariate analysis used chi-square, and multivariate analysis used logistic regression with a full model approach. 3.1% of children had CFM (stunting and wasting). Factors associated with this case based on bivariate analysis (p-value <0.05) were child age, sex, mother's education, mother's occupation, food security, sanitation, socioeconomic status, weight measurement, and vitamin A administration. Factors associated with this case based on multivariate analysis were child age 36-47 months (OR=4.027; 95% CI=1.838-8.825; p-value=0.001), male (OR=1.832; CI=1.324-2.536; p< 0.000), child with Low Birth Weight (LBW) (OR=3.061; CI=1.879-4.986; p<0.000), and poorest socioeconomic status (quintile 1) (OR=3.109; CI=1.641-5.890; p<0.001).